Pelletizing analysis of cylinder pelletizer on MgO-fluxed pellets by discrete element method (DEM) - F. Yang; Zh. Tong; Sh. W. Zou; Zh. Y. Li; Z. J. Shen (Metalurgija, 2023)
Discrete Element Method (DEM) was used to analyze palletization process of MgO-fluxed pellets in cylinder pelletizer. The effects of the charge ratio and rotational speed of the cylinder pelletizer on the behavior of MgO-fluxed pellets were investigated by using the simulation. The simulation results show that under the condition of a certain gradient angle of the cylinder pelletizer (The gradient angle is 3°), the suitable parameters of the cylinder pelletizer are that the charge ratio is 3 % and the rotational speed N/ critical rotational speed NC is 0,3.